Cost variation analysis of oral anti-diabetic agents available in drug store of the tertiary care hospital and in Indian market - Chincholkar, Aparna; Pentewar, Ganesh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes, a chronic disorder and requires life-long treatment. Cost of drug treatment is a major hurdle related to medication compliance in Type 2 Diabetes Mellitus. The objective of the study was to find out the cost of antidiabetic drugs available in the drug store of a tertiary care hospital and compare it with the different brands of the same drugs available in Indian market. To evaluate the difference in cost of different brands of same active drug by calculating percentage variation of cost. Methods: Cost of single compound and combination compound oral antidiabetic drugs available in drug store and those same drugs in Indian market manufactured by different companies, in the same strength, number and dosage form. The percentage price variation between minimum and maximum cost of drugs were calculated. The percentage difference in cost of antidiabetic drugs available in drug store and in the Indian market was calculated. Results: The percentage price variation of oral antidiabetic drugs available in drug store was found to be as follows. In sulfonylureas, it was highest in Glimepiride (2mg) 1962, 96%, among biguindes, Metformin (500mg) 3012.5%, among alpha glucosidase inhibitors Voglibose (0.2mg) 387.17%. Voglibose (0.3mg) 361.30%. Among combination therapy Voglibose (0.3mg) + Metformin (500mg) 2809% showed maximum price variation. Conclusions: The average percentage price variation of different brands of the same drug is very wide and hence the physician must keep this in mind while prescribing since the drug treatment of type II diabetes mellitus is usually lifelong. Hence, manufacturing companies should aim to decrease the price variation while maintaining the therapeutic efficacy. Drug store of tertiary care hospital should try to provide the oral antidiabetic drug with least cost and sell the generic drugs.